2003
DOI: 10.2136/sssaj2003.1842
|View full text |Cite
|
Sign up to set email alerts
|

Compost Applications Increase Water‐Stable Aggregates in Conventional and No‐Tillage Systems

Abstract: two ways. First, fertilizers can increase crop production, leading to higher inputs of crop residues and more WSA Agricultural practices that alter the soil organic matter (SOM) than in unfertilized soils (Campbell et al., 2001). Second, content are expected to cause changes in soil stability and aggregation. soils amended with organic fertilizers such as legume The objective of this study was to evaluate short-term (Ͻ2 yr) changes in water-stable aggregates (WSA) in a silt-loam soil under different green manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 23 publications
6
69
0
4
Order By: Relevance
“…Past studies on the same soil type have shown that increases in MWD does not generally increase until SOC exceeds 2000 g m -2 (Carter 1992) and C inputs exceed 250 g m -2 yr -1 . Whalen et al (2003) found in a comparison of corn and soybean crops, that type of crop residue also affected aggregation as soybean was generally associated with a lower MWD than corn. In a comparison study of monoculture vs. rotation using liquid dairy manure, Bissonnette et al (2001) observed that MWD was closely associated with increasing levels of C inputs and concomitant increases in SOC.…”
Section: Residual Treatment Effect On Soil C and N Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…Past studies on the same soil type have shown that increases in MWD does not generally increase until SOC exceeds 2000 g m -2 (Carter 1992) and C inputs exceed 250 g m -2 yr -1 . Whalen et al (2003) found in a comparison of corn and soybean crops, that type of crop residue also affected aggregation as soybean was generally associated with a lower MWD than corn. In a comparison study of monoculture vs. rotation using liquid dairy manure, Bissonnette et al (2001) observed that MWD was closely associated with increasing levels of C inputs and concomitant increases in SOC.…”
Section: Residual Treatment Effect On Soil C and N Parametersmentioning
confidence: 96%
“…Water-stable particles showed no response to the LSM/mineral fertilizer treatments, except for the <0.25-mm particles which were greater under Treatment 2. Generally, increase of SOC via direct drilling, organic amendments or cropping tends to increase soil structural stability (Carter 1992;Bissonnette et al 2001;Whalen and Chang 2002;Whalen et al 2003), however, the increase depends on the original SOC level and the C input rate. In the present study, SOC was not increased at the 0-to 20-cm soil depth (mean and SE, 1730 g m -2 ± 67.0, Fig.…”
Section: Residual Treatment Effect On Soil C and N Parametersmentioning
confidence: 99%
“…Besides a substitution of energy and nutrients, and a stimulation of the internal processes in soil governed by the microbial community, the application of biowaste compost in agricultural soils may positively affect soil organic-matter (SOM) content and soil-aggregate stability (Balesdent et al, 2000;Wahlen et al, 2003) and thus may reduce the potential risk of soil erosion (Barthès and Roose, 2002;Leguédois and Le Bissonais, 2004;Cantón et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Annual nutrient applications included about 30 m 3 ha -1 of liquid dairy manure as well as 100 to 140 kg N ha -1 from urea fertilizer. Further description of the site has been provided by Whalen et al (2003) and Jiao et al (2004).…”
Section: Methodsmentioning
confidence: 99%